Influence of bacterial incorporation on mechanical properties of engineered cementitious composites (ECC) - Zhang, Zhigang (2019)
Incorporation of bacterial technology in concrete has attracted the attention of many researchers in the past decades. While much of the attention was focused on crack self-healing in concrete, it was also observed that such incorporation sometimes alters the mechanical properties of concrete significantly. There are very few studies related to the material performance of fiber reinforced concrete containing bacteria. In this paper, the bacteria were incorporated into engineered cementitious composites (ECC), and its mechanical properties were investigated systematically. At composite performance level, it was found that both compressive and tensile strength increased in bacteria-ECC, meanwhile the ECC with bacteria of higher activity presented more pronounced effect. Furthermore, crack pattern of ECC was also improved due to the addition of bacteria as smaller crack width was observed. In contrast, tensile strain capacity of bacteria-ECC reduced as compared with normal ECC, but still retained at high level. At microscale level, fracture toughness of matrix containing bacteria was higher than that of control mix. Additionally, matrix/fiber interface properties were altered in bacteria-ECC with lower chemical bond and higher frictional bond strength. The findings at microscale well explain the change in composite performance of ECCs based on micromechanics theory.